Turkish National Academic Network and Information Center - Yetkin, Serpil (Information World, 2003)
ULAKBIM was founded in 1996 as an institute of TUBITAK. ULAKBIM hastwo departments, being those of “UlakNet” and “Cahit Arf Information Center”. The purpose of ULAKBIM is to establish and manage the system, which would connect the universities and research institutions to international information highways, to provide the researchers with required scientific information and documents, to collect the nationwide produced knowledge and information, either through own or collaborative efforts, in order to develop databases for effective retrieval.
Keywords: ULAKBIM; UlakNet; Information centers; National Information Centers